Pontificia Academia Romana S. Thomae Aquinatis et Religionis Catholicae Pontificia Academia Theologica Romana - Sacchi, Mario Enrique (1994)
Fil: Sacchi, Mario Enrique. Armada Argentina. Escuela de Guerra Naval; Argentina